The Relationship Between Posttraumatic Cognitive Change, Posttraumatic Stress Disorder, and Posttraumatic Growth Among Chinese Adolescents After the Yancheng Tornado: The Mediating Effect of Rumination - Zhang, Yi; Xu, Wei; Yuan, Guangzhe; An, Yuanyuan (Frontiers in Psychology, 2018)
The aim of this study was to explore the different cognitive processes involved in the development of posttraumatic stress disorders (PTSDs) and posttraumatic growth (PTG). One year after the Yancheng tornado, 455 middle school students were assessed to study how posttraumatic cognitive change (PCC) influenced PTSD and PTG among traumatized Chinese adolescents through the role of rumination. The results indicated that intrusive rumination partly mediated the relationship between PCC and PTSD, and deliberate rumination partly mediated the relationship between PCC and PTSD and completely mediated the relationship between PCC and PTG. These results suggest that the cognitive processes of PTSD and PTG are different. Furthermore, the study also suggests that PTSD and PTG can coexist in individuals. This study may offer some suggestions for clinical practice after traumatic events.